Richard Lee: The Politics, Art and Science of Anthropology - Gailey, Christine Ward (Anthropologica, 2022)
This introduction to the work of Richard B. Lee provides both a biographical sketch and an examination of major contributions his research has made to anthropology today. The biographical sketch of Richard B. Lee situates his development as a political anthropologist in the 1960s. The intellectual biography addresses his involvement in key debates about foraging peoples, the historicity of primitive communism, the social construction of gender and gender hierarchies, four-fields approaches in anthropology, and the role of the anthropologist in indigenous rights.